TIPE DAN PROPORSI SALURAN PEMASARAN KOMODITI IKAN LAYANG (Decapterus spp) PADA PELABUHAN PERIKANAN SAMUDERA KENDARI - Siang, Roslindah Daeng; Nur, Andi Irwan; Salika, Salika; Annaastasia, Nurhuda; Patiung, Seventry Meliana (Jurnal Perikanan Pantura (JPP), 2024)
This study aims to determine the type and proportion of marketing channels for flying fish commodities (Decapterus spp). This research was carried out in January-February 2024 at the Samudera Fisheries Port, Puday Village, Abeli District, Kendari City, Southeast Sulawesi Province. Data collection techniques are conducted through interviews with fishermen marketing actors, commission agents, retailers, inter-regional and industrial traders. The data analysis used is descriptive analysis. The results of the study show that there are five types of marketing channels. Type I fishermen - commission agents - retailers - consumers, type II fishermen - commission agents - inter-regional traders - consumers, type III fishermen - commission agents - industry - consumers, type IV fishermen - commission agents - consumers PPS, type V fishermen - commission agents – industry - domestic consumers. Local marketing channels consist of types I to IV, while type V is a domestic marketing channel. The proportion of marketing shows that 60% of the total marketing is for the local market, while 40% is for the domestic market. The structure and proportion of the marketing channel of the flyfish can be the basis for the development of a more efficient marketing strategy in the future.